An overview on the typology of shophouses’ façade at the heritage area in Ipoh City / Wan Nordiana Wan Ali, Nurul Huda Abdul Hadi and Noor Rizallinda Ishak - Wan Nordiana, Wan Ali; Nurul Huda, Abdul Hadi; Noor Rizallinda, Ishak (2015)
Ipoh is the capital of Perak and is located in the Northern part of Peninsular Malaysia. Ipoh was well- known for being the largest tin producing region in the world during the early 1900s. The tin-mining activity led the Chinese from Mainland China to migrate to this region. The presence of this community, which has a close relationship with the British, influenced the trading activity and the architectural development of Ipoh which is now referred to as the heritage area of Ipoh. The heritage area of Ipoh City consists of the core zone and buffer zone and has been gazetted on the 18th of December 2014 due to provision of Town and Country Planning Act (Act 172). The architectural asset of the heritage area of Ipoh is the uniqueness of shophouses that reflects the variety of colonial styles and the glory of the tin mining industry during that era. Therefore, this research is carried out to identify the typology of the building façade at the heritage area of Ipoh City. A pilot survey had been conducted to collect the primary data and supported by reports, government publications, textbooks, journals, interview sessions and others. The finding shows that there are six architectural styles of heritage building façade that were categorized by referring to the characteristics and elements identified. As a conclusion, this research may create awareness among the public and relevant parties on the significance of preserving the heritage building for future generation.